EAGBRP: A Gateway Based Routing Protocol for Heterogeneous Wireless Sensor Networks (Journal of Scientific Research, 2021)
In most of the cluster-based routing protocols for wireless sensor networks (WSNs), cluster heads (CHs) are selected from the normal sensors which may expire rapidly due to fast energy diminution for such an additional workload. As a consequence, the network lifetime of such cluster-based routing protocol reduces drastically. To resolve these constraints, in this study, we proposed a gateway-based routing protocol-namely Energy-Aware Gateway Based Routing Protocol (EAGBRP) for WSNs. In our proposed protocol, the deployed sensor nodes of a WSN were divided into five logical regions based on their location in the sensing field. The base station (BS) was installed out of the sensing area, and two gateway nodes were inaugurated at two predefined regions of the sensing area. The CH in each region is independent of the other regions and selected based on a weighted election probability. We implemented our proposed routing protocol through simulations. To evaluate the performance of our EAGBRP, we simulated SEP, M-GEAR, and MGBEHA (4GW) protocols. The network lifetime, throughput, and residual energy parameters are utilized for performance analysis. It is revealed from the performance analysis results that WSNs with EAGBRP achieve maximum network lifetime and throughput over other considered protocols with minimum energy consumption.